Long-term follow-up of the pCONus device for the treatment of wide-neck bifurcation aneurysms. Issue 4 (August 2022) - Guenego, Adrien; Mine, Benjamin; Bonnet, Thomas; Elens, Stephanie; Vazquez Suarez, Juan; Jodaitis, Lise; Ligot, Noémie; Naeije, Gilles; Lubicz, Boris
Purpose: Wide-neck bifurcation aneurysms remain challenging for the neurointerventionist and/or neurosurgeon despite many recent advances. The pCONus (Phenox, Bochum, Germany) is an emerging device for endovascular neck protection, we report the first long-term results of this device. Methods: We performed a retrospective analysis of all consecutive intracranial wide-neck bifurcation aneurysms treated with the pCONus. Patients' characteristics were reviewed, procedural complications, angiographic (Roy-Raymond scale) and clinical outcomes were documented. Results: Between January 2016 and September 2019, 43 patients (74% female, median age 56 [49–66] years) with 43 wide-neck bifurcation aneurysms (mean width of 6.8 ± 2.1 mm, dome/neck ratio of 1.3 ± 0.2 and neck of 5.2 ± 1.3 mm) were included. A procedural angiographic complication was reported in five patients (12%), no patient presented a post-operative neurological deficit or long-term complication, mortality rate was 0%. At last follow-up (median of 46.5 months [38.3–51.7]), an adequate occlusion (complete and neck remnant) was observed in 37/43 patients (86%) and an aneurysm remnant in 6/43 (14%). Four patients (9%) needed retreatment. No in-stent stenosis or branch occlusion was depicted. Conclusion: pCONus device provides a safe and efficient alternative for endovascular wide-neck bifurcation aneurysms management, with long-term stability.